A Development of an Attendance System based on Facial Recognition Approach - Lo, Zhan Preston; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2021)
The punch card attendance recording system used by Chau Sui Teck (Mawar) Sdn Bhd supermarket company currently does not provide an automated attendance process. The company typically use punch card systems to keep employee attendance records for employment purposes. However, in line with the rapid development of technology, important data recording and storage methods such as attendance and working hours of staff need to be improved so that analysis and related work processes can be done more efficiently. The existing system does not perform automatic salary calculations, is unable to generate warning letters to employees immediately, is unable to record data simultaneously. All these difficulties will cause the process of recording attendance and employment of employees to be inefficient. Thus, a presence system using face recognition for Chau Sui Teck Sdn. Bhd. was developed to overcome the stated problems. The Administrators and users of the respective systems are the managers and employees of the company. The prototype model is used as a software development guide. This system includes five main modules namely user login & registration, face recognition, data management, data analysis, notifications and reporting. The Local Binary Pattern History (LBPH) algorithm is implemented into the system to handle the face recognition process. The Python, PHP, SQL programming languages and MySQL database are used to produce this system. The result of this project is a fully automated attendance system that will conduct attendance checks on all employees on each working day. The system developed is also expected to be able to perform salary calculations at the end of each month, can produce a reminder letter when necessary, can record many attendances at one time, and data will be taken in real time.